Finite Math Examples
[11131-31-2-5]⎡⎢⎣11131−31−2−5⎤⎥⎦
Step 1
Write the matrix as a product of a lower triangular matrix and an upper triangular matrix.
[100l2110l31l321][u11u12u130u22u2300u33]=[11131-31-2-5]⎡⎢⎣100l2110l31l321⎤⎥⎦⎡⎢⎣u11u12u130u22u2300u33⎤⎥⎦=⎡⎢⎣11131−31−2−5⎤⎥⎦
Step 2
Step 2.1
Two matrices can be multiplied if and only if the number of columns in the first matrix is equal to the number of rows in the second matrix. In this case, the first matrix is 3×33×3 and the second matrix is 3×33×3.
Step 2.2
Multiply each row in the first matrix by each column in the second matrix.
[1u11+0⋅0+0⋅01u12+0u22+0⋅01u13+0u23+0u33l21u11+1⋅0+0⋅0l21u12+1u22+0⋅0l21u13+1u23+0u33l31u11+l32⋅0+1⋅0l31u12+l32u22+1⋅0l31u13+l32u23+1u33]=[11131-31-2-5]⎡⎢⎣1u11+0⋅0+0⋅01u12+0u22+0⋅01u13+0u23+0u33l21u11+1⋅0+0⋅0l21u12+1u22+0⋅0l21u13+1u23+0u33l31u11+l32⋅0+1⋅0l31u12+l32u22+1⋅0l31u13+l32u23+1u33⎤⎥⎦=⎡⎢⎣11131−31−2−5⎤⎥⎦
Step 2.3
Simplify each element of the matrix by multiplying out all the expressions.
[u11u12u13l21u11l21u12+u22l21u13+u23l31u11l31u12+l32u22l31u13+l32u23+u33]=[11131-31-2-5]⎡⎢⎣u11u12u13l21u11l21u12+u22l21u13+u23l31u11l31u12+l32u22l31u13+l32u23+u33⎤⎥⎦=⎡⎢⎣11131−31−2−5⎤⎥⎦
[u11u12u13l21u11l21u12+u22l21u13+u23l31u11l31u12+l32u22l31u13+l32u23+u33]=[11131-31-2-5]⎡⎢⎣u11u12u13l21u11l21u12+u22l21u13+u23l31u11l31u12+l32u22l31u13+l32u23+u33⎤⎥⎦=⎡⎢⎣11131−31−2−5⎤⎥⎦
Step 3
Step 3.1
Write as a linear system of equations.
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u11=3l21u11=3
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u11=1l31u11=1
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
Step 3.2
Solve the system of equations.
Step 3.2.1
Replace all occurrences of u11u11 with 11 in each equation.
Step 3.2.1.1
Replace all occurrences of u11u11 in l21u11=3l21u11=3 with 11.
l21⋅1=3l21⋅1=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u11=1l31u11=1
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
Step 3.2.1.2
Simplify the left side.
Step 3.2.1.2.1
Multiply l21l21 by 11.
l21=3l21=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u11=1l31u11=1
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
l21=3l21=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u11=1l31u11=1
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
Step 3.2.1.3
Replace all occurrences of u11u11 in l31u11=1l31u11=1 with 11.
l31⋅1=1l31⋅1=1
l21=3l21=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
Step 3.2.1.4
Simplify the left side.
Step 3.2.1.4.1
Multiply l31l31 by 11.
l31=1l31=1
l21=3l21=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
l31=1l31=1
l21=3l21=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
l31=1l31=1
l21=3l21=3
u11=1u11=1
u12=1u12=1
u13=1u13=1
l21u12+u22=1l21u12+u22=1
l21u13+u23=-3l21u13+u23=−3
l31u12+l32u22=-2l31u12+l32u22=−2
l31u13+l32u23+u33=-5l31u13+l32u23+u33=−5
Step 3.2.2
Replace all occurrences of l31l31 with 11 in each equation.
Step 3.2.2.1
Replace all occurrences of l31l31 in l31u12+l32u22=-2l31u12+l32u22=−2 with 1.
1⋅u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
l31u13+l32u23+u33=-5
Step 3.2.2.2
Simplify the left side.
Step 3.2.2.2.1
Multiply u12 by 1.
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
l31u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
l31u13+l32u23+u33=-5
Step 3.2.2.3
Replace all occurrences of l31 in l31u13+l32u23+u33=-5 with 1.
1⋅u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
Step 3.2.2.4
Simplify the left side.
Step 3.2.2.4.1
Multiply u13 by 1.
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u12+u22=1
l21u13+u23=-3
Step 3.2.3
Replace all occurrences of l21 with 3 in each equation.
Step 3.2.3.1
Replace all occurrences of l21 in l21u12+u22=1 with 3.
3⋅u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u13+u23=-3
Step 3.2.3.2
Simplify the left side.
Step 3.2.3.2.1
Multiply 3 by u12.
3u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u13+u23=-3
3u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l21u13+u23=-3
Step 3.2.3.3
Replace all occurrences of l21 in l21u13+u23=-3 with 3.
3⋅u13+u23=-3
3u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.3.4
Simplify the left side.
Step 3.2.3.4.1
Multiply 3 by u13.
3u13+u23=-3
3u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
3u13+u23=-3
3u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
3u13+u23=-3
3u12+u22=1
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.4
Replace all occurrences of u12 with 1 in each equation.
Step 3.2.4.1
Replace all occurrences of u12 in 3u12+u22=1 with 1.
3(1)+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.4.2
Simplify the left side.
Step 3.2.4.2.1
Multiply 3 by 1.
3+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
3+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
u12+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.4.3
Replace all occurrences of u12 in u12+l32u22=-2 with 1.
1+l32u22=-2
3+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.4.4
Simplify the left side.
Step 3.2.4.4.1
Remove parentheses.
1+l32u22=-2
3+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
1+l32u22=-2
3+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
1+l32u22=-2
3+u22=1
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.5
Replace all occurrences of u13 with 1 in each equation.
Step 3.2.5.1
Move all terms not containing u22 to the right side of the equation.
Step 3.2.5.1.1
Subtract 3 from both sides of the equation.
u22=1-3
1+l32u22=-2
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.5.1.2
Subtract 3 from 1.
u22=-2
1+l32u22=-2
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
u22=-2
1+l32u22=-2
3u13+u23=-3
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.5.2
Replace all occurrences of u13 in 3u13+u23=-3 with 1.
3(1)+u23=-3
u22=-2
1+l32u22=-2
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.5.3
Simplify the left side.
Step 3.2.5.3.1
Multiply 3 by 1.
3+u23=-3
u22=-2
1+l32u22=-2
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
3+u23=-3
u22=-2
1+l32u22=-2
u13+l32u23+u33=-5
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.5.4
Replace all occurrences of u13 in u13+l32u23+u33=-5 with 1.
1+l32u23+u33=-5
3+u23=-3
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.5.5
Simplify the left side.
Step 3.2.5.5.1
Remove parentheses.
1+l32u23+u33=-5
3+u23=-3
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1+l32u23+u33=-5
3+u23=-3
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1+l32u23+u33=-5
3+u23=-3
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.6
Replace all occurrences of u22 with -2 in each equation.
Step 3.2.6.1
Move all terms not containing u23 to the right side of the equation.
Step 3.2.6.1.1
Subtract 3 from both sides of the equation.
u23=-3-3
1+l32u23+u33=-5
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.6.1.2
Subtract 3 from -3.
u23=-6
1+l32u23+u33=-5
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
u23=-6
1+l32u23+u33=-5
u22=-2
1+l32u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.6.2
Replace all occurrences of u22 in 1+l32u22=-2 with -2.
1+l32⋅-2=-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.6.3
Simplify the left side.
Step 3.2.6.3.1
Move -2 to the left of l32.
1-2l32=-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1-2l32=-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1-2l32=-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7
Replace all occurrences of u23 with -6 in each equation.
Step 3.2.7.1
Move all terms not containing l32 to the right side of the equation.
Step 3.2.7.1.1
Subtract 1 from both sides of the equation.
-2l32=-2-1
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.1.2
Subtract 1 from -2.
-2l32=-3
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
-2l32=-3
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.2
Divide each term in -2l32=-3 by -2 and simplify.
Step 3.2.7.2.1
Divide each term in -2l32=-3 by -2.
-2l32-2=-3-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.2.2
Simplify the left side.
Step 3.2.7.2.2.1
Cancel the common factor of -2.
Step 3.2.7.2.2.1.1
Cancel the common factor.
-2l32-2=-3-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.2.2.1.2
Divide l32 by 1.
l32=-3-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l32=-3-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l32=-3-2
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.2.3
Simplify the right side.
Step 3.2.7.2.3.1
Dividing two negative values results in a positive value.
l32=32
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l32=32
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
l32=32
u23=-6
1+l32u23+u33=-5
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.3
Replace all occurrences of u23 in 1+l32u23+u33=-5 with -6.
1+l32⋅-6+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.7.4
Simplify the left side.
Step 3.2.7.4.1
Move -6 to the left of l32.
1-6l32+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1-6l32+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1-6l32+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.8
Replace all occurrences of l32 with 32 in each equation.
Step 3.2.8.1
Replace all occurrences of l32 in 1-6l32+u33=-5 with 32.
1-6(32)+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.8.2
Simplify the left side.
Step 3.2.8.2.1
Simplify 1-6(32)+u33.
Step 3.2.8.2.1.1
Simplify each term.
Step 3.2.8.2.1.1.1
Cancel the common factor of 2.
Step 3.2.8.2.1.1.1.1
Factor 2 out of -6.
1+2(-3)(32)+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.8.2.1.1.1.2
Cancel the common factor.
1+2⋅(-3(32))+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.8.2.1.1.1.3
Rewrite the expression.
1-3⋅3+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1-3⋅3+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.8.2.1.1.2
Multiply -3 by 3.
1-9+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
1-9+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.8.2.1.2
Subtract 9 from 1.
-8+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
-8+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
-8+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
-8+u33=-5
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.9
Move all terms not containing u33 to the right side of the equation.
Step 3.2.9.1
Add 8 to both sides of the equation.
u33=-5+8
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.9.2
Add -5 and 8.
u33=3
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
u33=3
l32=32
u23=-6
u22=-2
l31=1
l21=3
u11=1
u12=1
u13=1
Step 3.2.10
Solve the system of equations.
u33=3l32=32u23=-6u22=-2l31=1l21=3u11=1u12=1u13=1
Step 3.2.11
List all of the solutions.
u33=3,l32=32,u23=-6,u22=-2,l31=1,l21=3,u11=1,u12=1,u13=1
u33=3,l32=32,u23=-6,u22=-2,l31=1,l21=3,u11=1,u12=1,u13=1
u33=3,l32=32,u23=-6,u22=-2,l31=1,l21=3,u11=1,u12=1,u13=1
Step 4
Substitute in the solved values.
[11131-31-2-5]=[1003101321][1110-2-6003]